A CaZnOS-MgF2 heterojunction stress luminescent material and preparation method thereof
By constructing CaZnOS-MgF2 heterojunction stress luminescent material, combining doping ions and regulating molar ratio, the problems of insufficient luminescent intensity of a single matrix elastic stress luminescent material and opacity of composites are solved, and high-brightness and transparent stress luminescent material are achieved, expanding its application range.
Patent Information
- Application Number
- CN202311327375.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-10-13
AI Technical Summary
In the prior art, the luminous intensity of the elastic stress luminescent materials based on a single matrix is insufficient, and the composite elastomer is opaque, which limits its application range.
By constructing CaZnOS-MgF2 heterojunction stress luminescent material, the heterojunction structure of MgF2 and CaZnOS is used to combine doped ions such as Mn, Tb, Pr, Nd, and Yb to regulate the molar ratio and doping ratio of the material, improve the luminescent performance and realize a transparent matrix.
It realizes high-bright stress luminescence, and the material can be made into transparent or translucent composites, which are widely used in visual pressure sensing, intelligent anti-counterfeiting, electronic signatures and other fields.
Smart Images

Figure CN117384621B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and in particular to a CaZnOS-MgF2 heterojunction stress luminescent material and a preparation method thereof. Background Art
[0002] Stress luminescence refers to the dynamic luminescence phenomenon produced by solid materials under various mechanical forces (such as twisting, pressing, stretching, breaking, etc.). Compared with photoluminescence and electroluminescence, the above two require additional light sources and power supplies, while stress luminescence can realize the conversion of mechanical energy into light energy under the action of mechanical force. Therefore, stress luminescence materials are energy-saving and environmentally friendly smart materials. According to the differences in the excitation mode and stress luminescence mechanism of stress luminescence materials, stress luminescence can be divided into elastic deformation luminescence and inelastic luminescence. Among them, the stress luminescence material based on elastic luminescence can be restored to its original state after the application of pressure, and its luminescence performance can still remain stable after the pressure, and it can be reused; and within a large pressure range, its stress luminescence intensity has a good linear relationship with the applied pressure, so the elastic deformation stress luminescence material has broad application prospects in visual stress sensing, intelligent anti-counterfeiting, flexible electronic devices, etc. In order to better meet the development of stress visualization devices, there is an urgent need to develop high-brightness stress luminescence devices.
[0003] So far, many elastic stress luminescent materials and systems have been studied and explored, but most of the elastic stress luminescent materials that have been reported are based on a single matrix to explore their stress luminescent properties. Currently, there are few heterojunction stress luminescent materials and systems that have been developed, and further development is needed. In 2020, the applicant's research group reported: Construction of ZnS / CaZnOS heterojunction to achieve high-efficiency mechanical light-light energy conversion: Advanced Materials, 2020, 32(16): 1907747, successfully proving that constructing a heterojunction is an effective method to achieve high-brightness stress luminescence. In 2023, based on this method, we realized the high-brightness intelligent stress luminescence of CaZnOS-ZnS-SrZnOS ternary heterojunction: Materials & Design, 2023, 225: 111589. At the same time, we also realized 3D printing of high-brightness stress luminescence complexes for ZnS / CaZnOS binary heterojunction and CaZnOS-ZnS-SrZnOS ternary heterojunction: Advanced Science, 2023, 10(3), 2204925; Additive Manufacturing, 2023, 73, 103695. Subsequently, we also realized stress luminescence enhancement based on ZnO-ZnF2-based heterojunction with the cooperation team: Advanced Functional Materials, 2023: 2301372. This shows that the luminescence performance of elastic stress luminescence materials with a single matrix can be further improved, so that it can be more widely used.
[0004] In summary, the problems existing in the prior art are as follows: the luminescence intensity of elastic stress luminescent materials based on a single matrix still needs to be improved, and the bulk obtained after most inorganic stress luminescent systems are composited with organic elastomers does not have transparent properties. At present, the inorganic stress luminescence that can achieve transparent or translucent composite organic elastomers is extremely limited. It is reported that the only inorganic stress luminescent system that can obtain transparent or translucent composite organic silicone is a fluoride matrix (Science Bulletin, 2023, 67 (7), 707-715). However, the stress luminescence of monomer fluoride matrices, such as MgF2, is weaker than that of stress luminescent matrices such as sulfur oxides such as CaZnOS. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a CaZnOS-MgF2 heterojunction stress luminescent material and its preparation method and application, so as to solve the technical problems of single matrix elastic stress luminescent material, insufficient luminescent intensity and opaque composite elastomer.
[0006] The present invention provides the following technical solutions:
[0007] The present invention provides a CaZnOS-MgF2 heterojunction stress luminescent material. The chemical general formula of the heterojunction stress luminescent composite material is mCaZnOS-nMgF2:xM, wherein M is a doping ion, which is a single element or a combination of multiple elements selected from Mn, Tb, Pr, Nd, and Yb, and m, n, and x represent the molar numbers of CaZnOS, MgF2, and M, respectively.
[0008] MgF2 and CaZnOS construct a heterojunction, and both can form heterojunction stress luminescent materials after doping with Mn and various lanthanide metals (Tb, Pr, Nd, Yb); at the same time, MgF2 is a fluoride, which can be used as a flux in the reaction process to increase the stability of the material. Moreover, the prepared stress luminescent material can make a transparent matrix, which has a wider range of applications. The ultra-wide bandgap characteristics of MgF2 can enable stress quantum tailoring in heterojunction stress luminescent materials.
[0009] Furthermore, in the heterojunction stress luminescent composite material, m:n=8:1-1:8, x:(x+m+n)=(0.1-2):100.
[0010] The photoluminescence center wavelength of materials with different ratios of CaZnOS and MgF2 shows a wide shift, which can be controlled by adjusting the ratio of CaZnOS and MgF2.
[0011] If the doping ion content is too little, the luminescence center is insufficient, resulting in low brightness; if the doping ion content is too much, it will cause luminescence quenching. When the doping ion content is within the above range, it can serve as the luminescence center in the mechanoluminescent composite material, improve the luminescence performance, and the luminescence color can be adjusted by changing the type of doping ions.
[0012] Furthermore, m:n=5:4.
[0013] Further, x:(x+m+n)=1:100.
[0014] Furthermore, the doping ions use carbonate compounds or chlorides of corresponding metals as raw materials.
[0015] Furthermore, the CaZnOS uses ZnS and CaCO3 as raw materials.
[0016] The present invention also provides a method for preparing the above-mentioned CaZnOS-MgF2 heterojunction stress luminescent material, comprising the following steps:
[0017] S1. Weigh the raw materials according to the molar ratio of the target product, mix them evenly, add anhydrous ethanol, grind them evenly into powder, and dry them to obtain a mixed powder;
[0018] S2, placing the mixed powder in a reactor to react and obtain a powder;
[0019] S3. After the powder is naturally cooled, it is taken out and ground evenly into a powdery state to obtain the CaZnOS-MgF2 heterojunction stress luminescent material.
[0020] Furthermore, the drying is carried out in an oven at 80-100° C. for 5-10 minutes.
[0021] Furthermore, the mixed powder is placed in a reaction furnace for reaction as follows: the mixed powder is heated in an inert atmosphere in the reaction furnace, the temperature is increased to 1000-1400° C. at a heating rate of 1-20° C. / min, and the mixture is sintered, and the mixture is kept warm for 4-8 hours and then cooled naturally along with the furnace.
[0022] Furthermore, m:n=8:1~1:8, x:(x+m+n)=(0.1~2):100.
[0023] The present invention also provides a composite elastomer, which is a transparent or semi-transparent sheet made by forming a composite of the stress luminescent material and an optically transparent organic macromolecular elastic material.
[0024] The optically transparent organic polymer elastic material is PET or PDMS.
[0025] The present invention also provides applications of the above-mentioned CaZnOS-MgF2 heterojunction stress luminescent material, and the application of the CaZnOS-MgF2 heterojunction stress luminescent material in the fields of visualized pressure sensing, intelligent anti-counterfeiting, electronic signature, flexible wearable devices, motion monitoring, display, and biomedicine.
[0026] The present invention has the following beneficial effects:
[0027] 1. The CaZnOS-MgF2 wide bandgap semiconductor and ultra-wide bandgap fluoride CaZnOS-MgF2 heterojunction stress luminescent material prepared by the present invention, both the MgF2 and CaZnOS used can realize stress luminescence by doping with Mn and various lanthanide metals (Tb, Pr, Nd, Yb), and MgF2 is a fluoride, which can be partially used as a flux in the reaction process, and the binding force of fluorine ions is strong. The incorporation of fluorine can also increase the stability of the material, and the prepared stress luminescent material can make a transparent matrix, which has a wider range of applications, and the ultra-wide bandgap characteristics of MgF2 make it possible for stress quantum tailoring of the heterojunction stress luminescent material;
[0028] 2. The present invention can realize the doping of some rare earth and transition ions, thereby realizing multi-color luminescence;
[0029] 3. The prepared stress luminescent powder is ground and sieved into a powder and mixed with an optically transparent organic polymer elastic material (PET or PDMS) to form a composite, which is made into a thin sheet or coated on the surface of the component to be tested. Under the action of external mechanical force, the stress of the composite or the component can be converted into light signal emission, thereby realizing direct energy conversion of force-light with adjustable light intensity. It can be applied to visual pressure sensing, intelligent anti-counterfeiting, electronic signature, flexible wearable devices, motion monitoring, display, and biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 A flow chart of a method for preparing a CaZnOS-MgF2 heterojunction stress luminescent material provided in an embodiment of the present invention;
[0032] Figure 2 It is a characterization result diagram of the materials in Examples 1 to 9 and Comparative Examples 1 to 2 of the present invention;
[0033] Figure 3 This is a physical picture of the stress luminescent composite material prepared in Example 4 of the present invention in a powder block state;
[0034] Figure 4 This is a graph showing the characterization results of the material in Example 10 of the present invention;
[0035] Figure 5 Schematic diagram of emission spectra of materials in Examples 1 to 9 and Comparative Examples 1 to 2 of the present invention at a wavelength of 280 nm;
[0036] Figure 6 This is a graph showing the characterization results of the material in Example 11 of the present invention;
[0037] Figure 7 This is a diagram showing the characterization results of the material in Example 12 of the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] An embodiment of the present invention provides a CaZnOS-MgF2 heterojunction stress luminescent material and a preparation method thereof. The general chemical formula of the CaZnOS-MgF2 heterojunction stress luminescent material is mCaZnOS-nMgF2:xM, wherein M is a doping ion, which is a single element or a combination of multiple elements selected from Mn, Tb, Pr, Nd, and Yb, and m, n, and x represent the molar numbers of CaZnOS, MgF2, and M, respectively.
[0040] In one embodiment, m:n may be 8:1, 7:2, 6:3, 5:4, 1:1, 4:5, 3:6, 2:7, 1:8, and x:(x+m+n) may be 0.1:100, 1:100, 1.5:100, 2:100.
[0041] In one embodiment, the doping ions are made of carbonate compounds or chlorides of corresponding metals.
[0042] In one embodiment, CaZnOS uses ZnS and CaCO3 as raw materials.
[0043] like Figure 1 As shown, the preparation method of the CaZnOS-MgF2 heterojunction stress luminescent material provided in the embodiment of the present invention comprises the steps of:
[0044] S101: selecting raw materials, wherein Ca and Mn use their carbonates as raw materials, Zn and S use their sulfides as raw materials, Tb, Pr, Nd, Yb and other elements use their chlorides as raw materials, weighing the raw materials of each element according to its stoichiometric ratio, then adding an appropriate amount of anhydrous ethanol to the mixed raw materials, grinding and mixing in an agate mortar, and drying in an oven at 80-100° C. to obtain a mixed powder;
[0045] S102: placing the evenly ground powder in an alumina crucible, heating it to 1000-1400°C at a heating rate of 10-20°C / min in an inert atmosphere, burning it for 4-8 hours, and cooling it naturally with the furnace;
[0046] S103: Grind the obtained cooled powder, and sieve it through a 300-mesh sieve to obtain the heterojunction stress luminescent material mCaZnOS-nMgF2:xM powder.
[0047] The application principle of the present invention is further described below in conjunction with specific embodiments.
[0048] Embodiments 1 to 9:
[0049] Taking CaZnOS-MgF2:1%Mn as an example, the specific sample ratio and raw material quality are shown in Table 1:
[0050] Table 1 Specific ratios and raw material qualities in each embodiment
[0051]
[0052] The mixed raw materials of the above formula are put into an agate mortar, anhydrous ethanol is added, and the mixture is ground and mixed evenly, and then dried in an oven at 80-100° C. to obtain a mixed powder; the evenly ground powder is placed in an alumina crucible, heated to 1000-1200° C. at a heating rate of 1-20° C. / min in an inert atmosphere, sintered for 4-8 hours, and cooled naturally with the furnace, and the obtained cooled powder is finely ground, and sieved through a 300 mesh / 150 mesh sieve to obtain a heterojunction stress luminescent material CaZnOS-MgF2:1%Mn powder.
[0053] Comparative Examples 1-2:
[0054] The specific ratio and raw material quality in the comparative example are shown in Table 2:
[0055] Table 2 Specific ratios and raw material quality in comparative examples
[0056]
[0057] The mixed raw materials of the above formula are placed in an agate mortar, anhydrous ethanol is added, and the mixture is ground and mixed evenly, and then dried in an oven at 80-100° C. to obtain a mixed powder; the evenly ground powder is placed in an alumina crucible, heated to 1000-1200° C. at a heating rate of 1-20° C. / min in an inert atmosphere, sintered for 4-8 hours, and cooled naturally with the furnace, and the obtained cooled powder is finely ground and sieved through a 300 mesh / 150 mesh sieve to obtain a single matrix CaZnOS: 1% Mn, MgF2: 1% Mn powder.
[0058] Embodiment 10:
[0059] Taking 5CaZnOS-4MgF2: 0.1%Mn, 1%Mn, 1.5%Mn, 2%Mn as an example, the specific operation steps are as follows:
[0060] Raw materials: during preparation, raw materials ZnS, CaCO3, MgF2, MnCO3, and CaCO3 are selected, and each element is weighed according to its stoichiometric ratio, and then an appropriate amount of anhydrous ethanol is added to the mixed raw materials, and ground in an agate mortar until the mixture is uniform, and then dried in an oven at 80-100°C to obtain a mixed powder;
[0061] Place the evenly ground powder in an alumina crucible, heat it to 1000-1200°C at a heating rate of 1-20°C / min in an inert atmosphere, sinter for 4-8 hours, and cool it down naturally with the furnace;
[0062] The obtained cooled powder was ground for 10-30 minutes, and sieved through a 300-mesh sieve to obtain heterojunction stress luminescent material CaZnOS-MgF2: 0.1% Mn, 1% Mn, 1.5% Mn, 2% Mn powder.
[0063] Embodiment 11:
[0064] Taking CaZnOS-MgF2: 1% Tb, 1% Yb as an example, the specific operation steps are as follows:
[0065] Raw materials: during preparation, raw materials ZnS, CaCO3, MgF2, TbCl3-6H2O, YbCl3-6H2O, and CaCO3 are selected, and each element is weighed according to its stoichiometric ratio, and then an appropriate amount of anhydrous ethanol is added to the mixed raw materials, and ground in an agate mortar until the mixture is uniform, and then dried in an oven at 80-100°C to obtain a mixed powder;
[0066] Place the evenly ground powder in an alumina crucible, heat it to 1000-1200°C at a heating rate of 1-20°C / min in an inert atmosphere, sinter for 4-8 hours, and cool it down naturally with the furnace;
[0067] The obtained cooled powder was ground for 10-30 minutes, and sieved through a 300-mesh sieve to obtain a heterojunction stress luminescent material CaZnOS-MgF2: 1% Tb, 1% Yb powder.
[0068] Embodiment 12:
[0069] Taking CaZnOS-MgF2: 1% Tb, CaZnOS-MgF2: 1% Pr, CaZnOS-MgF2: 1% Nd as examples, the specific operation steps are as follows:
[0070] Raw materials: during the preparation, raw materials ZnS, CaCO3, MgF2, TbCl3-6H2O, PrCl3-6H2O, and NdCl3-6H2O are selected, and each element is weighed according to its stoichiometric ratio, and then an appropriate amount of anhydrous ethanol is added to the mixed raw materials, and the mixture is ground in an agate mortar until the mixture is uniform, and then dried in an oven at 80-100°C to obtain a mixed powder;
[0071] Place the evenly ground powder in an alumina crucible, heat it to 1000-1200°C at a heating rate of 1-20°C / min in an inert atmosphere, sinter for 4-8 hours, and cool it down naturally with the furnace;
[0072] The cooled powder was ground for 10-30 min, and sieved through a 300-mesh sieve to obtain heterojunction stress luminescent materials CaZnOS-MgF2: 1% Tb, CaZnOS-MgF2: 1% Pr, and CaZnOS-MgF2: 1% Nd powders, respectively.
[0073] Test analysis
[0074] X-ray diffraction analysis was performed on the powder materials obtained in Examples 1, 4, and 9, the powder materials obtained in Comparative Examples 1 to 2, CaZnOS, and MgF2, respectively;
[0075] The stress luminescent powders prepared in each embodiment are respectively composited with an optically transparent organic polymer elastic material (PET or PDMS) to prepare devices to test stress luminescent properties;
[0076] Specifically, stress luminescence characteristics test: the luminescence spectrum of the prepared stress luminescence composite material is tested using a homemade spectrometer-dynamometer-sliding motor. First, the prepared stress luminescence test sheet is attached to a glass sheet fixed vertically in a homemade stress luminescence test device, and the pressure applied by the sliding motor to the test sheet is set. The sliding motor is then used to slide left and right perpendicular to the sheet. During the sliding process, the light emitted by the composite stress luminescence material will be collected and transmitted to the spectrometer through optical fiber, and finally the luminescence intensity of the composite stress luminescence material is collected.
[0077] Test results see Figure 2 to Figure 7 , now explained as follows:
[0078] Figure 2In the figure, (a) is a schematic diagram of the X-ray diffraction patterns of the powder materials prepared in Examples 1, 4, and 9 of the present invention, the powder materials prepared in Comparative Examples 1 to 2, and CaZnOS and MgF2, indicating that CaZnOS and MgF2 are well compounded by preparation; (b) is a schematic diagram of the stress luminescence spectrum of the CaZnOS-MgF2 heterojunction stress luminescent materials in various proportions in Examples 1 to 9, indicating that under a force of 30N, the emission wavelength of the stress luminescence is about 595nm; (c) is a schematic diagram of the stress luminescence integral intensity comparison of the CaZnOS-MgF2 heterojunction stress luminescent materials in various proportions in Examples 1 to 9 at 400-750nm. By comparison, it can be obtained that the composite heterojunction stress luminescent material with a ratio of 5:4 has the strongest stress luminescence integral intensity and the best stress luminescence performance; (d) The heterojunction stress luminescent material with the optimal ratio of CaZnOS-MgF2:1%Mn has the strongest stress luminescence integral intensity and the best stress luminescence performance. Schematic diagram of the stress luminescence spectrum comparison between the luminescent material and the stress luminescent materials of single matrix CaZnOS: 1% Mn and MgF2: 1% Mn, indicating that the stress luminescence emission wavelength of CaZnOS: 1% Mn is 611nm, the stress luminescence emission wavelength of the heterojunction stress luminescent material with the optimal ratio of CaZnOS-MgF2: 1% Mn is 595nm, and the stress luminescence emission wavelength of MgF2: 1% Mn is 597nm; (e) Schematic diagram of the stress luminescence integrated intensity comparison between the heterojunction stress luminescent material with the optimal ratio of CaZnOS-MgF2: 1% Mn and the stress luminescent materials of single matrix CaZnOS: 1% Mn and MgF2: 1% Mn at 400-750nm. By comparison, it can be found that the stress luminescence intensity and stress luminescence performance can be effectively improved by compositely constructing a heterojunction of CaZnOS and MgF2.
[0079] Figure 3 This is a real picture of the 5CaZnOS-4MgF2:1%Mn, CaZnOS-MgF2 heterojunction stress luminescent material in the powder block state provided in Example 4 of the present invention. In a bright environment, its stress luminescent effect can still be observed with the naked eye, indicating that its stress luminescent performance is excellent.
[0080] Figure 4 This is the stress luminescence intensity curve of the 5CaZnOS-4MgF2: 0.1% Mn, 1% Mn, 1.5% Mn, 2% MnCaZnOS-MgF2 heterojunction stress luminescent material provided in Example 10 of the present invention. By comparison, it can be seen that when Mn is doped at 1%, the stress luminescence performance of the stress luminescent composite material is the best.
[0081] Figure 5It is a schematic diagram of the emission spectra of various ratios of CaZnOS-MgF2:1%Mn, CaZnOS-MgF2 heterojunction stress luminescent materials of Examples 1 to 9 of the present invention and the powder materials of Comparative Examples 1 to 2 at an excitation wavelength of 280nm. By comparison, it can be found that when the ratio of CaZnOS and MgF2 is 8:1, the photoluminescence intensity is the strongest.
[0082] Figure 6 This is a schematic diagram of the stress luminescence spectrum of the heterojunction stress luminescent material of CaZnOS-MgF2: 1% Tb, 1% Yb provided in Example 11 of the present invention. The marked characteristic peaks at 300-700nm are the characteristic peaks of Tb, and the peak at 983nm is the characteristic peak of Yb, indicating that the composite heterojunction stress luminescent material can realize stress luminescence co-doped with rare earth elements Tb and Yb.
[0083] Figure 7 In the figure, (a) is a schematic diagram of the stress luminescence spectrum of the CaZnOS-MgF2:1%Tb heterojunction stress luminescent material provided in Example 12 of the present invention; (b) is a schematic diagram of the stress luminescence spectrum of the CaZnOS-MgF2:1%Pr heterojunction stress luminescent material provided in Example 12 of the present invention; (c) is a schematic diagram of the stress luminescence spectrum of the CaZnOS-MgF2:1%Nd heterojunction stress luminescent material provided in Example 12 of the present invention, indicating that the composite heterojunction stress luminescent material can realize stress luminescence of single doping of Tb, Pr and Nd.
[0084] It can be seen from the above test results that the CaZnOS-MgF2 wide bandgap semiconductor and ultra-wide bandgap fluoride CaZnOS-MgF2 heterojunction stress luminescent material prepared by the present invention, by adjusting the ratio of CaZnOS and MgF2, the ratio of doped ions is controlled, and the obtained material can be observed by naked eyes in a bright environment. The thin slices made by mixing the material with PET or PDMS have changes in stress luminescence intensity of each sample under a certain stress, and the stress luminescence intensity is high, indicating that the material can be used as an excellent stress luminescent material; the present invention can achieve the doping of multiple rare earth and transition ions, and thus achieve multi-color luminescence; the prepared stress luminescent powder is ground and sieved into a powder and an optically transparent organic polymer elastic material (PET or PDMS) to form a composite, which is made into a thin slice or coated on the surface of the component to be tested. Under the action of mechanical external force, the stress of the composite or the component can be converted into light signal emission, realizing direct energy conversion of force-light with adjustable light intensity, and can be applied to the fields of visual pressure sensing, intelligent anti-counterfeiting, electronic signature, flexible wearable devices, sports monitoring, display, biomedicine, etc.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A CaZnOS-MgF2 heterojunction stress luminescent material, characterized in that: The chemical formula of the CaZnOS-MgF2 heterojunction stress luminescent material is mCaZnOS-nMgF2:xM, wherein M is a doping ion, which is a single element or a combination of multiple elements selected from Mn, Tb, Pr, Nd, and Yb, and m, n, and x represent the molar numbers of CaZnOS, MgF2, and M, respectively; m:n=8:1~1:8, x: (x+m+n)=(0.1~2):
100.
2. The CaZnOS-MgF2 heterojunction stress luminescent material according to claim 1, characterized in that: m:n=5:
4.
3. The CaZnOS-MgF2 heterojunction stress luminescent material according to claim 1, characterized in that: x: (x+m+n)=1:
100.
4. The CaZnOS-MgF2 heterojunction stress luminescent material according to claim 1, characterized in that: The CaZnOS uses ZnS and CaCO3 as raw materials; the doping ions use carbonate compounds or chlorides of corresponding metals as raw materials.
5. The method for preparing the CaZnOS-MgF2 heterojunction stress luminescent material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Weigh the raw materials according to the molar ratio of the target product, mix them evenly, add anhydrous ethanol, grind them evenly into powder, and dry them to obtain a mixed powder; S2, placing the mixed powder in a reactor to react and obtain a powder; S3. After the powder is naturally cooled, it is taken out and ground evenly into a powdery state to obtain the CaZnOS-MgF2 heterojunction stress luminescent material.
6. The method for preparing the CaZnOS-MgF2 heterojunction stress luminescent material according to claim 5, characterized in that: The drying is carried out in an oven at 80-100° C. for 5-10 minutes.
7. The method for preparing the CaZnOS-MgF2 heterojunction stress luminescent material according to claim 5, characterized in that: The mixed powder is placed in a reactor for reaction as follows: the mixed powder is heated in an inert atmosphere in the reactor, the temperature is raised to 1000-1400°C at a heating rate of 1-20°C / min, and the mixture is sintered, and the mixture is kept warm for 4-8 hours before being cooled naturally along with the furnace.
8. The method for preparing the CaZnOS-MgF2 heterojunction stress luminescent material according to claim 5, characterized in that: m:n=8:1~1:8, x: (x+m+n)=(0.1~2):
100.
9. The use of the CaZnOS-MgF2 heterojunction stress luminescent material according to any one of claims 1 to 4, characterized in that: The CaZnOS-MgF2 heterojunction stress luminescent material is used in the fields of visualized pressure sensing, intelligent anti-counterfeiting, electronic signature, flexible wearable devices, motion monitoring, display, and biomedicine.
Citation Information
Patent Citations
Short-wavelength blue high-brightness mechanoluminescence material and preparation method thereof
CN108467731A
Mechanoluminescence composite material as well as preparation method and application thereof
CN111909689A